Analysis of Factors that Impact Self Efficacy in Terms of Locus Control Learning Orientation and Work Environment Characteristics - Daud, Anshar; ., Djunaedi; Marliani, Lina; Kurniawanto, Hari; ., Fatmasari; Purnama, Chamdan (Journal of Ecohumanism, 2025)
This study aims to analyze the factors that impact self-efficacy, focusing on three key variables: locus of control, learning orientation, and work environment characteristics. Self-efficacy, the belief in one's ability to perform tasks and achieve goals, plays a crucial role in individual performance and organizational outcomes. Using a quantitative approach, data were collected through surveys distributed to a sample of employees across various industries. The findings reveal that locus of control and learning orientation significantly influence self-efficacy, with individuals who possess an internal locus of control and a strong orientation towards learning displaying higher levels of self-efficacy. Additionally, favorable work environment characteristics, such as support from management and opportunities for growth, also contribute to enhancing self-efficacy. These results suggest that organizations can improve employee performance by fostering a positive work environment and encouraging personal development through learning initiatives. The implications for both theoretical research and practical management strategies are discussed.